Impact of adherence to a lifestyle-integrated programme on physical function and behavioural complexity in young older adults at risk of functional decline: a multicentre RCT secondary analysis - Mikolaizak, A Stefanie (BMJ PUBLISHING GROUP, 2022)
10.1136/bmjopen-2021-054229